Managing the PSTN transformation a blueprint for a successful migration to IP-based networks - Dornheim, Sandra (CRC Press, 2015)
Filling this need, Managing the PSTN transformation: a blueprint for a successful migration to IP-based networks reflects the latest understanding of the challenges behind migrating customers from the old PSTN network to an IP infrastructure. The IP transformation blueprint described in this book is not a theoretical cookbook that describes how this could work. Instead, the book presents a blueprint that is the product of countless hours of work by hundreds of individuals at Deutsche Telekom (DT) over almost two years. The book presents insights gained as the DT team migrated the entire public switched telephone network in Macedonia to an Internet protocol-based platform